Orthogonal Control of Stability and Tunable Dry Adhesion by Tailoring the Shape of Tapered Nanopillar Arrays. (21st October 2015) - Cho, Younghyun; Kim, Gyuseok; Cho, Yigil; Lee, Su Yeon; Minsky, Helen; Turner, Kevin T.; Gianola, Daniel S.; Yang, Shu
Abstract : Tapered nanopillar structures of different cross‐sectional geometries including cone‐, pencil‐like, and stepwise are prepared from anodized aluminum oxide templates. The shape effect on the adhesion strength is investigated in experiments and simulation. Cone‐shaped nanopillars are highly bendable under load and can recover after unloading, thus, warranting high adhesion strength, 34 N cm −2 . The pencil‐like and stepwise nanopillars are, however, easily fractured and are not recoverable under the same conditions.